The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/pharmaceutics14051092
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Therapy of HER2-Expressing Xenografts Using the Second-Generation HER2-Targeting Affibody Molecule 188Re-ZHER2:41071

Abstract: HER2-targeted radionuclide therapy might be helpful for the treatment of breast, gastric, and ovarian cancers which have developed resistance to antibody and antibody-drug conjugate-based therapies despite preserved high HER2-expression. Affibody molecules are small targeting proteins based on a non-immunoglobulin scaffold. The goal of this study was to test in an animal model a hypothesis that the second-generation HER2-targeting Affibody molecule 188Re-ZHER2:41071 might be useful for treatment of HER2-expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In Affibody-mediated pretargeting, a therapeutic radionuclide is coupled to a small hapten with low reabsorption in kidneys [25,26]. The use of non-residualizing 131 I [27] and 188 Re [28] labels does not prevent reabsorption but promotes the very rapid release of radiometabolites of Affibody molecules from kidneys. A fusion with ABD and subsequent binding to albumin in vivo makes an Affibody-containing therapeutic construct bigger than 65 kDa and prevents or reduces its passage through the glomerular membrane [15].…”
Section: Discussionmentioning
confidence: 99%
“…In Affibody-mediated pretargeting, a therapeutic radionuclide is coupled to a small hapten with low reabsorption in kidneys [25,26]. The use of non-residualizing 131 I [27] and 188 Re [28] labels does not prevent reabsorption but promotes the very rapid release of radiometabolites of Affibody molecules from kidneys. A fusion with ABD and subsequent binding to albumin in vivo makes an Affibody-containing therapeutic construct bigger than 65 kDa and prevents or reduces its passage through the glomerular membrane [15].…”
Section: Discussionmentioning
confidence: 99%
“…Dewulf et al, from the university of Antwerp, reported a novel RANKL PET imaging agent, [ 64 Cu]Cu-NOTA-denos-Fab, that allows for fast tumor imaging with improved imaging contrast when compared with its antibody counterpart, showing promise as a potential PET RANKL imaging tool for future clinical applications [ 3 ]. Researchers from the university of Uppsala further illustrated the potential of radiolabeled affibody molecules for both diagnostic and therapeutic applications, with promising results [ 4 , 5 , 6 ].…”
mentioning
confidence: 99%